EVALUASI PROSES PENGEMBANGAN KURIKULUM MERDEKA DI SD MUHAMMADIYAH 02 MEDAN MEDAN - Ahmad Tarmizi Hasibuan; Nadiyah Nasution; Asita Maya Sari; Ainun Sofiah; Murni Khoiriyah (Al Ittihadu, 2026)
The Merdeka Curriculum is the Indonesian government's latest policy aimed at recovering learning post-COVID-19 pandemic and improving the quality of human resources. The implementation of this curriculum in Muhammadiyah elementary schools faces various . challenges, especially in the process of developing operational curricula at the educational unit level. This research aims to evaluate the curriculum development process of Merdeka Curriculum at SD Muhammadiyah 02 Medan by focusing on teacher readiness, infrastructure, paradigm shifts in learning, as well as assessment and evaluation systems. The research method uses a qualitative approach with literature study and field observation. The results show that the development of the Merdeka Curriculum at SD Muhammadiyah 02 Medan still faces significant obstacles, including uneven teacher readiness, limited infrastructure and educational facilities, a paradigm shift from teacher-centered to student-centered that has not been fully understood, and an assessment system that is still oriented towards cognitive aspects. The main inhibiting factors include teachers' limited understanding of authentic assessment, high administrative burdens, and minimal school system support. However, SD Muhammadiyah 02 Medan has shown commitment in implementing the Merdeka Curriculum through teacher training, utilization of learning technology, and strengthening Islamic character based on Muhammadiyah values. This research concludes that strengthening teacher competencies, improving infrastructure, and providing ongoing mentoring are needed so that the Merdeka Curriculum development process at SD Muhammadiyah 02 Medan can run effectively and achieve the expected learning objectives.